Pengembangan Aplikasi Berbasis Mobile Untuk Pengamanan Teks Menggunakan Metode Advanced Encryption Standard dan Least Significant Bit - Priandana, Bhisma Satwika Ari; Widiartha, I Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p61, 2022)
The rapid development of technology is very influential in all aspects of life. Data is one of the most sensitive and important things in today's technological developments. In this regard, data security is very important for system developers and system users. Cryptography and steganography are options for securing data where cryptography supports security aspects such as data integrity, data confidentiality which makes messages have no real meaning and also eliminates suspicion of messages sent. The results showed that the combination of the AES cryptographic method and the LSB steganography method was very well used to secure messages and the results also showed that there was no difference between the original image and the encoded image.